PERENCANAAN STRUKTUR BAWAH DAN RENCANA ANGGARAN BIAYA PADA PEMBANGUNAN JEMBATAN GANTUNG KELAS SATU KECAMATAN SETU - Rizki Adityo Saputro; Ninik Paryati, Eko Darma, Rika Sylviana (CV. ADIBA AISHA AMIRA, 2024)
The foundation is a basic medium of building construction that functions as a successor to the heavy force owned by the building structure that is supported to the soil layer, thus in every planning of a civil building it is expected that the foundation structure is always taken into account in detail and complex. In planning a construction project, cost plays an important role in project implementation. Therefore, project cost budget planning needs to be designed and prepared properly based on an estimation concept so as to produce an accurate and economical cost estimate value. In this study, the researcher planned the foundation using the CPT (Conus Penetration Test) method and calculated the cost budget by referring to PERMEN PUPR No.26 of 2016 concerning Guidelines for Price Analysis of Unit Work in the Public Works Sector, while scheduling used the Barchart and Curve S methods. The results of the study obtained that the type of foundation used was a triangle pile type pile foundation with a size of 28x28 cm with the calculation of the bearing capacity of the foundation permit using the Begemann formula to get a value = 4,393 tons. The planned cost budget needed for the planning of the Class 1 Suspension Bridge in Setu District, Bekasi Regency is Rp 13,137,312,000 (Thirteen Billion One Hundred and Thirty Seven Three Hundred and Twelve Million Rupiah) with a duration of 12 weeks or 90 working days.